Research on Resource Pool for Carrierˊs Service Platform Based on Cloud Computing - Yongjin Liu; Ke Huang (Dianxin kexue)
In the construction process of service platforms, carriers generally face issues of low hardware resource utilization, high operation and maintenance costs, high energy consumption, long construction period and so on. As cloud computing matures, using virtualization technology to build a cloud computing resource pool, carrying on the carrier's service platforms has become an important way for platform integration. Cloud computing technology service model were outlined, on basis of which platform resource pool's position was cleared. Then according to characters of the service network, an implementation strategy of platform integration based on cloud computing platform was proposed. Then from a real case, a construction program for cloud computing resource pool including hardware devices configuration and virtualization software selection was provided.